[Retracted] Contamination of Hospital Water Supplies in Gilan, Iran, with Legionella pneumophila, Escherichia coli, and Pseudomonas aeruginosa - Ahmadi Jalali Moghadam, Masoumeh; Honarmand, Hamidreza; Asfaram Meshginshahr, Sajad (Interdisciplinary Perspectives on Infectious Diseases, 2015)
This study is designed to determine the contamination degree of hospital water supplies with Pseudomonas aeruginosa, Legionella pneumophila, and E. coli in Gilan, Iran. Samples were collected directly into sterile containers and concentrated by centrifuge. Half part of any sample transferred to yeast extract broth and the second part transferred to Trypticase Soy Broth and incubated for 3 days. DNA was extracted by using commercial kit. Four rounds of PCR were performed as follows: multiplex PCR for detecting Pseudomonas aeruginosa, Integron 1, and Metallo-β-lactamases gene; PCR for detecting Legionella pneumophila and mip gene separately; PCR for detecting E. coli; and another PCR for detecting whole bacterial presence. Contamination rates of cold, warm, and incubator water samples with P. aeruginosa, were 16.6%, 37.5%, and 6.8% consequently. Degrees of contamination with L. pneumophila were 3.3%, 9.3%, and 10.9% and with E. coli were zero, 6.2%, and zero. Total bacterial contamination of cold, warm, and incubator water samples was 93.3%, 84.4%, and 89.0% consequently. Metallo-β-lactamases gene was found in 20.0% of all samples. Contamination degree with P. aeruginosa was considerable and with L. pneumophila was moderate. Metallo-β-lactamases gene was found frequently indicating widespread multiple drug resistance bacteria. We suggest using new decontamination method based on nanotechnology.